Respon Siswa Terhadap Pembelajaran Daring Penjasorkes - Yossita Wisman; Uket Uket; Cukei Cukei; Yogi Saputra (FKIP Universitas Palangka Raya, 2022)
Physical Education Learning is said to be successful if all objectives predetermined learning can be achieved (Abdulkadir, 2001). But deep in fact, there are still schools that have the results of Physical Education learning low who have not reached the predetermined standard of completeness. So is the case for grade Vb SDN 6 Palangka City Palangka Raya based on the results interviews with teachers of the Physical Education subject showed that the results Learning Physical Education for some students is not as expected or less than the predetermined standard which is 75. By using Online Learning method, students are expected to have a high interest in learning. This research was conducted online and according to a qualitative approach which is expected to improve and improve the quality of the process and results student learning in studying Physical Education. Time This research was conducted in July-September 2020/2021 Academic Year. This Research Place held at SDN 6 Palangka which is located on Jl. Tjilik Riwut Km. 1. The class It was used as a research location for the Vb class of SDN 6 Palangka, Palangka City Kingdom. The research subjects were students in class Vb SUN 6 Palangka with the number of students 30 people. Data collection techniques from research are questionnaires (questionnaire) and The data on the students' physical education learning outcomes test with learning online learning obtained from the Physical Education subject teacher. Once every 3 months at SDN 6 Palangka is carried out by Semester Offset Test (UTS) to find out the arrival where students' understanding of the physical education and physical education learning has been done taught. The results of this study indicate that the Physical Education learning response questionnaire data students with online learning in class Vb SDN 6 Palangka, Palangka Raya City that is, an average of 84.17 /% is very good based on results and washing out In this study it can be concluded that prior to online learning the results an average of 72.13 after Physical Education learning with online learning give positive and very good results, seen from the emergence of the criteria The assessment set and the average score of the assessment are very good. Middle Semester Deuteronomy (UTS) which aims to find out understanding Students of Physical Education lessons with online learning show results which was very good with an average score of 82.24. Learning outcomes are very good, no regardless of the student's response to the learning. If students respond to the learning is positive, the results obtained will be good and even increase 10.11 from before.